Potret Pembelajaran Pendidikan Islam Pada Anak Tunagrahita Di Sekolah Luar Biasa Bhakti Pemuda Kota Kediri - Novie Putri Amalia; Makhfud (Indonesian Journal of Islamic Education Studies (IJIES), 2019)
This article discusses how the learning of Islamic Religious Education for mentally retarded children in Extraordinary Schools (SLB). Extraordinary Schools (SLB) are special schools for school-age children who have "special needs". Children with intellectual disabilities have IQs below the average normal child in general, thus causing their intellectual and intellectual functions disrupted which causes other problems that arise during their development. Islamic education is not only given to normal children, but also to children who have disabilities or mental disorders. This study uses qualitative research and uses a phenomenological approach. Data collection methods are observation, interviews, and documentation. The results of this study state that the implementation of Islamic Religious Education learning for mentally retarded children in SLB Bhakti Pemuda City of Kediri emphasizes memorization and practice directly with concrete or tangible objects, and is evaluated in three domains, namely cognitive, affective, and psychomotor. However, the evaluation of learning in SLB Bhakti Pemuda Kota Kediri is more measured from the realm of affective (attitude and values) and psychomotor (skills or skills).